DESPITE THE FACT THAT THERE IS CURRENTLY CLEAR HYPERTENSION TREATMENT STRATEGY, WHY DOES BP CONTROL RATES REMAIN POOR WORLDWIDE? (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
Despite the fact that the causes of hypertension have been studied at the molecular level and precise treatment strategies have been developed, the level of blood pressure control remains low worldwide. What could be the reason? This article is about that.